1993
DOI: 10.1097/00006842-199303000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors associated with cardiovascular reactivity in older adults.

Abstract: This study examined associations of psychosocial factors with cardiovascular reactivity in two groups of men and women--spouse caregivers of individuals with Alzheimer's disease (M age = 69.4 N = 82) and controls (M age = 68.5, N = 78) group-matched for age and gender. Cardiovascular responses to an emotional task (speech sample about one's spouse) yielded higher systolic and diastolic blood pressures (SBP, DBP) than a spoken cognitive task, which in turn yielded higher BPs and heart rate (HR) than the baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(65 citation statements)
references
References 92 publications
2
63
0
Order By: Relevance
“…However, Vitaliano, Russo, Paulsen, & Bailey (1995) examined cardiovascular recovery from laboratory stressors in older adults, and found that avoidance coping was positively related to diastolic blood pressure and heart rate. The same laboratory also found similar findings among caregivers of Alzheimer patients (Vitaliano et al, 1993). Controlling for standard risk factors such as smoking, avoidance coping was associated with higher levels of cardiovascular reactivity.…”
Section: Coping and Biomedical Outcomessupporting
confidence: 55%
“…However, Vitaliano, Russo, Paulsen, & Bailey (1995) examined cardiovascular recovery from laboratory stressors in older adults, and found that avoidance coping was positively related to diastolic blood pressure and heart rate. The same laboratory also found similar findings among caregivers of Alzheimer patients (Vitaliano et al, 1993). Controlling for standard risk factors such as smoking, avoidance coping was associated with higher levels of cardiovascular reactivity.…”
Section: Coping and Biomedical Outcomessupporting
confidence: 55%
“…Another study reported that caregivers who look after an Alzheimer's patient with little social support evidenced reactive heart rates during emotionally charged conversations [16] . Yet another study emphasized that hostility, anger, avoidance without coping, type A behavior, and emotionality in caregivers of Alzheimer's patients were related to cardiovascular reactivity [17] . Chronic stress increases the risk of hypertension in caregivers of Alzheimer's patients [18,19] .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in other areas of care such as dementia or cancer, it was found that caregivers had higher risk of cardiovascular disease, [30][31][32] an impaired immunity that could compromise healing [33][34][35][36] and even a higher mortality than the general population, between older spouses. 37 Since caregivers of ALS patients are subject to a large overhead and increased risk of depression and anxiety, this led us thinking that more studies need to be made to clarify such aspects.…”
Section: Amp Student Artigo De Revisãomentioning
confidence: 99%